TELAAH SISTEM MANAJEMEN PENGAMANAN HOTEL DALAM PENANGANAN KEADAAN DARURAT KEBAKARAN DI HOTEL X SEMARANG (STUDI KASUS DI BAGIAN KITCHEN) - Zalffarona Jihantama; Bina Kurniawan; Baju Widjasena (Jurnal Kesehatan Masyarakat (Undip), 2018)
Hotel X is a four-star hotel that has 12 floors with a risk of fire. In 2015, there was a small fire in the kitchen. Fire was caused by a fire that ignites to the ducting exhaust which was dirty by the amount of fat produced by the cooking process. In order to reduce the risk of fire in hotels, the government issued special regulations for hotels about the hotel security management system which included handling fire emergencies and must be fulfilled by every hotel. The purpose of this study was to examine the fulfillment of the hotel security management system in handling fire emergencies at Hotel X Semarang. This research was qualitative research with observation methods and in-depth interviews. Subjects in this study were 3 main informants and 2 triangulation informants. The results of this study indicated that there was already a procedure for handling fire emergencies in Hotel X, the procedure has also been regularly tested through training for emergency response teams, except that there was no process of hazard identification and procedure review. The fire protection system was not optimal in its availability, conditions, and functions. Maintenance of equipment has been carried out by engineers routinely every once a month, but specifically, fire extinguisher maintenance has been carried out by security. Hotels are advised to provide resources and training to identify fire hazards, complete fire protection systems, and conduct procedure reviews.